Aligning Core Brand Values (CBV) and Corporate Social Responsibility (CSR) to Enhance Corporate Brand Equity (CBE): A Non - Monetary Approach - Nandan, Shiva; Nandan, Monica (Indian Journal of Marketing, 2014)
The present paper offers a practical approach for building or strengthening a corporate brand. An entirely "end-user focused" and "solely profit-maximization" perspective of conducting business may not be conducive for corporate brands in today’s global economy, where consumers are environmentally and socially conscious. The concepts of, and relationship between, core brand values (CBV) and corporate social responsibility (CSR) are discussed. We proposed that compatibility between CSR and CBV - which satisfies multiple stakeholders without sacrificing financial viability of an organization - can promote an organization’s corporate brand equity (CBE). We presented two propositions relating CBV and CSR and provided illustrations of companies where CSR activities are congruent with CBV. The unique contribution of this paper is the novel suggestion of enhancing CBE through compatibility between CBV and CSR.